Análisis para el establecimiento de un país de la UNASUR para la exportación de cítricos deshidratados. - Cordova Malla, Jhonatan Santiago (My University, 2018)
The countries to generate foreign exchange must consider international trade as an objective, elaborating products and services that are demanded in other countries, contributing to the development of the productive sector. The entrepreneur who seeks to expand their commercialization frontiers must carry out studies or analysis to estimate the country that has the economic and market characteristics that demand their product or service. Ecuador has the export of non-traditional products that little by little seek their space contributing to the growth of the export sector. One of these products is the dehydrated fruit that has a growing demand in countries like the United States and the European Union, wishing to know the needs within the Union of South Nations UNASUR. The general objective of the work is to prepare ananalysis for the establishment of a UNASUR country for the export of dehydrated citrus. The methodology of applied research is the descriptive one of cross section using data of qualitative type to know the needs of the external market. The bibliographic technique was applied to access primary sources such as scientific journals, books, internet, whose information served to raise this work. The competitive advantage of this study is to establish the processes that must be followed to determine attractive external markets for non-traditional Ecuadorian products, giving the entrepreneur the opportunity to seek new markets outside the border limits.
Los países para generar divisas deben de considerar al comercio internacional como objetivo elaborando productos y servicios que sean demandados en otros países contribuyendo al desarrollo del sector productivo. El empresario que busca ampliar sus fronteras de comercialización ha de realizar estudios o análisis para estimar el país que tenga las características económicas y de mercado que demanden su producto o servicio. Ecuador cuenta con la exportación de productos no tradicionales que de a poco buscan su espacio contribuyendo al crecimiento del sector exportador. Uno de estos productos lo constituye la fruta deshidratada que posee una demanda creciente en países como Estados Unidos y la Unión Europea, deseándose conocer las necesidades dentro de la Unión de Naciones Suramericanas (UNASUR).El objetivo general del trabajo es elaborar un análisis para el establecimiento de un país de la UNASUR para la exportación de cítricos deshidratados. La metodología de investigación aplicada es la descriptiva de corte transversal utilizando datos de tipo cualitativo para conocer las necesidades del mercado externo. Se aplicó la técnica bibliográfica para tener acceso a fuentes primarias tales como revistas científicas, libros, internet, cuya información sirvió para levantar el presente trabajo. La ventaja competitiva del presente estudio es establecer los procesos que se deben de seguir para determinar mercados externos atractivos para los productos no tradicionales ecuatorianos dando la oportunidad al empresario a buscar nuevos mercados fuera de los límites fronterizos.
Keywords: COMERCIO INTERNACIONAL; EXPORTACIÓN; UNASUR; CÍTRICOS DESHIDRATADOS; DEMANDA